Naringin Protects against Tau Hyperphosphorylation in Aβ25–35-Injured PC12 Cells through Modulation of ER, PI3K/AKT, and GSK-3β Signaling Pathways. (15th February 2023) - Qiu, Qi; Lei, Xia; Wang, Yueying; Xiong, Hui; Xu, Yanming; Sun, Huifeng; Xu, Hongdan; Zhang, Ning
Abstract : Alzheimer's disease (AD) is the most common form of dementia and a significant social and economic burden. Estrogens can exert neuroprotective effects and may contribute to the prevention, attenuation, or even delay in the onset of AD; however, long-term estrogen therapy is associated with harmful side effects. Thus, estrogen alternatives are of interest for countering AD. Naringin, a phytoestrogen, is a key active ingredient in the traditional Chinese medicine Drynaria. Naringin is known to protect against nerve injury induced by amyloid beta-protein (A β ) 25–35, but the underlying mechanisms of this protection are unclear. To investigate the mechanisms of naringin neuroprotection, we observed the protective effect on A β 25–35 -injured C57BL/6J mice's learning and memory ability and hippocampal neurons. Then, an A β 25–35 injury model was established with adrenal phaeochromocytoma (PC12) cells. We examined the effect of naringin treatment on A β 25–35 -injured PC12 cells and its relationship with estrogen receptor (ER), phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT), and glycogen synthase kinase (GSK)-3 β signaling pathways. Estradiol (E2 ) was used as a positive control for neuroprotection. Naringin treatment resulted in improved learning and memory ability, the morphology of hippocampal neurons, increased cell viability, and reduced apoptosis. We next examined the expression of ER β, p-AKT (Ser473, Thr308), AKT, p-GSK-3 β (Ser9), GSK-3 β, p-Tau (Thr231, Ser396), and Tau in PC12 cells treated with A β 25–35 and either naringin or E2, with and without inhibitors of the ER, PI3K/AKT, and GSK-3 β pathways. Our results demonstrated that naringin inhibits A β 25–35 -induced Tau hyperphosphorylation by modulating the ER, PI3K/AKT, and GSK-3 β signaling pathways. Furthermore, the neuroprotective effects of naringin were comparable to those of E2 in all treatment groups. Thus, our results have furthered our understanding of naringin's neuroprotective mechanisms and indicate that naringin may comprise a viable alternative to estrogen therapy.